Prevalence and trends in tobacco use, secondhand smoke exposure at home and household solid fuel use among women in 57 low- and middle-income countries, 2000-2018 - Yang Lili L; Wu Han; Zhao Min; Magnussen Costan G; Xi Bo (PERGAMON-ELSEVIER SCIENCE LTD, 2022)
Background: Tobacco use, secondhand smoke (SHS) exposure and household solid fuel use in women of reproductive age can cause morbidity and mortality for both women and offspring.
Objectives: We aimed to determine the prevalence of tobacco use, SHS exposure at home and household solid fuel use among women in low- and middle-income countries (LMICs) and their secular trends between 2000 and 2018.
Methods: We used the most recent data from the Demographic and Health Surveys in 57 LMICs (n = 1,598,111) that were completed between 2010 and 2018 to assess the prevalence of tobacco use, SHS exposure at home and household solid fuel use among women of reproductive age (15-49 years). We also used data from 41 selected LMICs that had data from two or more surveys completed between 2000 and 2018 to assess secular trends in the prevalence of tobacco use and household solid fuel use among women.
Results: In 2010-2018, the overall prevalence of tobacco use, daily SHS exposure at home and household solid fuel use among women in 57 LMICs was 3.2% (95 %CI = 3.1-3.3), 23.0% (22.8-23.2), and 65.6% (65.3-65.9), respectively. The prevalence of tobacco use was lower among pregnant women than non-pregnant women (2.1% vs. 3.3%), but the prevalence of daily SHS exposure at home (24.4% vs. 22.8%) and household solid fuel use (69.1% vs. 65.3%) was higher among pregnant women than non-pregnant women. About 16% of the women presented two or three simultaneous risk factors. Between 2000 and 2018, the prevalence of tobacco use decreased in 24 (64.9%) of 37 countries, and the prevalence of household solid fuel use decreased in 20 (50.0%) of 40 countries.
Conclusions: Tobacco use among women was much low in LMICs, but SHS exposure at home was more common. Although the prevalence of household solid fuel use decreased over time in most LMICs, these recent estimates remained unacceptably high.